Exploring the relationship between sport demand's key players and environmental sustainability: pointers from a systematic review - Martins, Rute (2021)
A systematic literature review was conducted to explore the relation between key players of the demand for sport and the environmental sustainability, within the 2013-2019 timeframe. Data were collected from four scientific databases and scrutinized by the PRISMA protocol. Quantitative systematic literature review and content analysis, supported by Nvivo 11 and EndNote X7 software, were the methodologies used for data analysis. The results provided by the 142 selected studies highlighted tourism and recreation as the most scrutinized areas by recent research on this relationship. Compared to spectators and local residents, the nature-based sport practitioners were the furthest analysed type of sport consumers. The most pursued research objective relates to the behavioural driving factors. Among the environmental action's encouraging causes, psychological factors were emphasized. Promoting the sport consumer's environmental education, along with the improvement of the environmental communication developed by the organizations integrating the sport offer, were the greatest management recommendations to induce ecological behavioural change. Future studies should focus on deepening the knowledge on the spectators' and local residents' relation with environmental sustainability, namely through the comparison of practitioners and non-practitioners, so that sport can assert itself more effectively in the implementation of environmental sustainability.